Webster's encyclopedic unabridged dictionary of the english languaje (New York : Gramercy Books, 1993)
Although not eveyone may realize it, the origen of the English languaje can be dated with relative precision. The term English goes back to the name of one of the Germanic tribes the angles woho, according to the venerable. Bede, began to indade Britain in the year 449 english derives from" Angle-ish." and both the name of the tribe.
1. Atals of the world 2. Chronology of Mayor Dates in History 3. Presidents of the United State 4. Vice Presidents of the United State 5. The Declaration of independence 6. The Constitución of the United States 7. A manual of style 8. The bad speller Dictionary
Incluye Weights and measures
Incluye Crossword Puzzle Dictionary
Keywords: ENCICLOPEDIA Y DICCIONARIOS; ENCICLOPEDIA DE INGLÉS